Patient‐important outcomes other than mortality in recent ICU trials: Protocol for a scoping review. Issue 7 (24th June 2021) - Granholm, Anders; Kaas‐Hansen, Benjamin Skov; Kjær, Maj‐Brit Nørregaard; Anthon, Carl Thomas; Sivapalan, Praleene; Schjørring, Olav Lilleholt; Andersen, Lars W.; Mathiesen, Ole; Strøm, Thomas; Jensen, Aksel Karl Georg; Perner, Anders; Møller, Morten Hylander
Abstract: Background: Randomised clinical trials (RCTs) conducted in intensive care units (ICUs) frequently focus on all‐cause mortality, but other patient‐important outcomes are increasingly used and recommended. Their use, however, is not straightforward: choices and definitions, operationalisation of death, handling of missing data, choice of effect measures, and statistical analyses for these outcomes vary greatly. Methods: We will conduct a scoping review in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses Extension for Scoping Reviews. We will search 10 selected general and speciality journals for RCTs conducted in adult ICU patients from 2018 and onwards reporting at least 1 patient‐important outcome other than mortality (including days alive without life support/days alive and out of hospital‐type outcomes, health‐related quality of life, functional/cognitive/neurological outcomes, and other general patient‐important outcomes). We will summarise data on outcome measures and definitions, assessment time points, proportions and handling of death, proportions and handling of missing data, and effect measures and statistical methods used for analysis. Discussion: The outlined scoping review will provide an overview of choices, definitions and handling of patient‐important outcomes other than mortality in contemporary RCTs conducted in adult ICU patients. This may guide discussions with patients and relatives, the design of future RCTs, and research on optimal outcome choices and handling.